Reprints of Rare Papers on Mollusca: Muller, 1774, Vermium Terrestrium Et Fluviatilium (Continued from Sterkiana 62) - Otto Friedrich Müller (Hello World!, 1977)
Anyone interested in land and freshwater Mollusca has encountered and perhaps deciphered the cryptic 'Mull., Verm. Terr.' and soon finds out that this refers to the great work by Otto Friedrich Müller on the non-marine Mollusca of Denmark. Müller mentions the snails and clams of Europe and even gives their vernacular names but at first sight it seems incongruous to find his name attached to North American species. The fact is that his Danish species were not all confined to Europe but were holarctic in distribution and his work was useful not only to European workers but also to that small band of American malacologists who were collecting and describing American mollusks in the early nineteenth century. The need to consult Müller from time to time still makes itself felt but it is a lucky malacologist who has easy access to Müller's book. It seemed a good idea, therefore, to reprint it serially in Sterkiana and to print some extra copies to bind together later on. The book has some 230 pages and is well within the space limitations of five or six numbers of Sterkiana. (Cont.)